2008
DOI: 10.1524/ract.2008.1535
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Zr(IV), Th(IV) and Pu(IV) hydrous oxides in CaCl2solutions and the formation of ternary Ca-M(IV)-OH complexes

Abstract: Zirconium / Thorium / Plutonium / Ternary Ca-M(IV)-OH complexes / Solubility / Thermodynamics / SIT Summary. The solubility of Zr(IV), Th(IV) and Pu(IV) hydrous oxides is investigated at 22 ± 2 • C in alkaline 0.1-4.5 M CaCl 2 solutions. Further studies are performed with Zr(IV) over the entire pH range in NaCl and CaCl 2 media, and with Zr(IV) and Th(IV) in alkaline Ca(ClO 4 ) 2 solutions. The comparison of Zr(IV) data in different ionic media (NaCl, NaClO 4 , CaCl 2 and Ca(ClO 4 ) 2 ) of similar ionic streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 26 publications
6
44
1
Order By: Relevance
“…Sparingly soluble ternary Ca-Np(V)-OH and quaternary Ca-Np(V)-OH-Cl solid phases were found to control the solubility of Np within the investigated pH m -range (8)(9)(10)(11)(12) and CaCl 2 concentrations (0.25-4.5 M). The authors observed also the formation of very stable ternary Ca x NpO 2 (OH) y 1+2x-y species in the aqueous phase (x = 1 and 3; y = 2 and 5), in line with previous studies available for An(III) and An(IV) in alkaline CaCl 2 solutions [40][41][42]. No further experimental studies dedicated to shed light on the relevant topic of Np(V) solubility and hydrolysis in NaCl systems have been reported after the discussion between Neck and Rao.…”
Section: Introductionsupporting
confidence: 89%
“…Sparingly soluble ternary Ca-Np(V)-OH and quaternary Ca-Np(V)-OH-Cl solid phases were found to control the solubility of Np within the investigated pH m -range (8)(9)(10)(11)(12) and CaCl 2 concentrations (0.25-4.5 M). The authors observed also the formation of very stable ternary Ca x NpO 2 (OH) y 1+2x-y species in the aqueous phase (x = 1 and 3; y = 2 and 5), in line with previous studies available for An(III) and An(IV) in alkaline CaCl 2 solutions [40][41][42]. No further experimental studies dedicated to shed light on the relevant topic of Np(V) solubility and hydrolysis in NaCl systems have been reported after the discussion between Neck and Rao.…”
Section: Introductionsupporting
confidence: 89%
“…It clearly showed the known XRD pattern of Nd(OH) 3 (cr) (JCPDSFile 70-0214). The experimental and analytical procedures and the chemicals used to prepare the matrix solutions were the same as in previous studies and described therein [10,11]. The samples for the solubility measurements were prepared and stored at 22 ± 2 °C in an Ar glove box.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, our recent solubility measurements and spectroscopic studies with Zr(IV), Th(IV), Pu(IV), Nd(III), and Cm(III) in alkaline CaCl 2 solutions [9][10][11][12] revealed a hitherto unknown phenomenon, the formation of ternary Ca-M-OH complexes with unusually high numbers of OH -ligands. The solubilities of ZrO 2 ؒxH 2 O(s) at pH = 10-12 in 0.1-2.0 M CaCl 2 and of ThO 2 ؒxH 2 O(s) at pH = 11-12 in 0.5-4.5 M CaCl 2 are raised to unexpectedly high values by the formation of the complexes Ca 3 [Zr(OH) 6 ] 4+ and Ca 4 [Th(OH) 8 ] 4+ , respectively, which could be identified and characterized by extended X-ray absorption fine structure spectroscopy (EXAFS) [9,10]. The equilibrium constants for these complexes were calculated in [10] with the specific ion interaction theory (SIT) [13] recommended in the NEA-TDB for ionic strength corrections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some potential repository settings, carbonate-poor and Ca-rich alkaline plumes may form owing to corrosion of cementitious waste forms. In these waters, tetravalent actinides form stable An-Ca-OH complexes (Altmaier et al, 2008;Fellhauer et al, 2010).…”
Section: Complexation and Solubilitymentioning
confidence: 99%